2009
DOI: 10.1242/dev.023564
|View full text |Cite
|
Sign up to set email alerts
|

Lessons from a gene regulatory network: echinoderm skeletogenesis provides insights into evolution, plasticity and morphogenesis

Abstract: Significant new insights have emerged from the analysis of a gene regulatory network (GRN) that underlies the development of the endoskeleton of the sea urchin embryo. Comparative studies have revealed ways in which this GRN has been modified (and conserved) during echinoderm evolution, and point to mechanisms associated with the evolution of a new cell lineage. The skeletogenic GRN has also recently been used to study the long-standing problem of developmental plasticity. Other recent findings have linked thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
78
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(81 citation statements)
references
References 74 publications
3
78
0
Order By: Relevance
“…Previous authors have characterized the DNG as an evolutionary novelty unique to all euechinoid echinoids (1,8,21), and our ancestral state reconstructions have revealed mean PPs that strongly identify the DNG as a novelty unique to all extant euechinoids. Nonetheless, our analysis also fails to demonstrate unambiguously that the last common ancestor of echinoids (including cidaroids) did not use the DNG, and instead used the mechanism present in extant cidaroids (8,21).…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Previous authors have characterized the DNG as an evolutionary novelty unique to all euechinoid echinoids (1,8,21), and our ancestral state reconstructions have revealed mean PPs that strongly identify the DNG as a novelty unique to all extant euechinoids. Nonetheless, our analysis also fails to demonstrate unambiguously that the last common ancestor of echinoids (including cidaroids) did not use the DNG, and instead used the mechanism present in extant cidaroids (8,21).…”
Section: Discussionsupporting
confidence: 61%
“…evolution | evo-devo | euechinoid | cidaroid | gene regulatory networks T he investigation of gene regulatory networks (GRNs) in modern taxa allows for the understanding of evolutionary changes in the regulatory genome that have underpinned the evolution of new morphological structures in deep time (1)(2)(3)(4). Establishing a timeline for the rates at which these novel structures arise, and the rate at which the developmental GRNs that encode them evolve, lies at the heart of evolutionary developmental biology (5).…”
mentioning
confidence: 99%
“…On the other hand, it is possible that the transformation of other cell lineages into PMCs occurred at the archenteron tip as a result of repression of PMC ingression in HpNanos-knockdown embryos. In fact, it has been reported that SMCs change their fate into skeletogenic mesenchyme cells when PMCs are removed (Ettensohn, 1990(Ettensohn, , 2008Hamada and Kiyomoto, 2003). As shown in Figure 4, in the knockdown chimera at the gastrula stage, micromere derived tracer-positive cells were detected in additional mesenchyme cells around the archenteron tip and skeletogenic mesenchyme cells.…”
Section: Role Of Hpnanos In the Regulation Of Cell Fate Specificationmentioning
confidence: 84%
“…Abundant comparative evidence exists for other euechinoid taxa as well, including Lytechinus variegatus (Lv) (31)(32)(33)(34)(35)(36)(37) and Paracentrotus lividus (Pl) (38)(39)(40)(41)(42). Data from these indirectdeveloping euechinoids indicate that although these taxa diverged from one another ∌90 mya (9, 43), very little appreciable change to their developmental GRNs has accrued (44)(45)(46). Although there is evidence of minor alterations to these GRNs, such as a heterochronic shift in snail expression in Lv and Sp (22), numerous studies have made clear the striking conservation of GRN linkages in these lineages.…”
mentioning
confidence: 99%